2016
DOI: 10.1186/s13287-016-0451-8
|View full text |Cite
|
Sign up to set email alerts
|

Grafted c-kit+/SSEA1− eye-wall progenitor cells delay retinal degeneration in mice by regulating neural plasticity and forming new graft-to-host synapses

Abstract: BackgroundDespite diverse pathogenesis, the common pathological change observed in age-related macular degeneration and in most hereditary retinal degeneration (RD) diseases is photoreceptor loss. Photoreceptor replacement by cell transplantation may be a feasible treatment for RD. The major obstacles to clinical translation of stem cell-based cell therapy in RD remain the difficulty of obtaining sufficient quantities of appropriate and safe donor cells and the poor integration of grafted stem cell-derived pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…The SCFR + donor cells survive up to 6 months in the subretinal space of host retina without generating teratoma. More importantly, in addition to robust material transfer and perfect cell replacement, these donor cells greatly inhibit the activation of microglia cells and improve the immune microenvironment of the RP disease (Chen et al, 2016;Zou et al, 2019). Our data well support the idea of SCFR + RPCs from a developmental view, and partially explain the advantages for transplantation, such as retinal multipotency, limited proliferation, strong survivability and proper migration.…”
Section: Discussionsupporting
confidence: 76%
“…The SCFR + donor cells survive up to 6 months in the subretinal space of host retina without generating teratoma. More importantly, in addition to robust material transfer and perfect cell replacement, these donor cells greatly inhibit the activation of microglia cells and improve the immune microenvironment of the RP disease (Chen et al, 2016;Zou et al, 2019). Our data well support the idea of SCFR + RPCs from a developmental view, and partially explain the advantages for transplantation, such as retinal multipotency, limited proliferation, strong survivability and proper migration.…”
Section: Discussionsupporting
confidence: 76%
“…55 Interestingly, KIT is not only expressed in LESCs but also in photoreceptors, lacrimal canaliculus epithelial stem cells and eye wall cells. [56][57][58] These cells are all essential for sustaining the physiological functions of the eye and are located in close proximity to SOX10-positive NCCs or their derivatives. 24 Hence, the SOX10-KIT-AKT axis may have a role in eye development and function beyond its role in maintaining LESCs that we demonstrated here.…”
Section: The Development and Maintenance Of Lescs Depends On Inter-mentioning
confidence: 99%
“…To characterize cell communication and gap junctions of photoreceptor‐like cells, we selected specific synaptic vesicle protein Synaptophysin to label the synaptic connections between regenerated photoreceptor‐like cells and adjacent neurons . Immunofluorescence assay showed that synaptophysin presented a multi‐layer distribution in the outer plexiform photoreceptor cells at the end and within the plexiform layer.…”
Section: Discussionmentioning
confidence: 99%